Incidencia de la implementación de las políticas de regeneración urbana en la apropiación del espacio público desde la perspectiva de las organizaciones sociales en el barrio La Ronda del Centro Histórico de la ciudad de Quito. - González León, Javier Nicolás (2014)
The position of Analytical Psychology has responded in advance to phenomena of social nature, which has expanded its analytical field and has enabled the approach to underserved areas or very little analyzed from this psychological stance. This research addressed the relationship between community members and youth groups Yaruquí parish, in this case, with particular emphasis on the archetype of the shadow......